Varicella-zoster virus (VZV) transcription during latency in human ganglia: detection of transcripts mapping to genes 21, 29, 62, and 63 in a cDNA library enriched for VZV RNA. - Cohrs, R J (1996)
Information on the extent of virus DNA transcription and translation in infected tissue is crucial to an understanding of herpesvirus latency. To detect low-abundance latent varicella-zoster virus (VZV) transcripts, poly(A)+ RNA extracted from latently infected human trigeminal ganglia was enriched for VZV transcripts by hybridization to biotinylated VZV DNA. After hybridization, the RNA-DNA hybrid was isolated by binding to avidin-coated beads and extensively washed, and the RNA was released by heat denaturation. A lambda-based cDNA library was then constructed from the enriched RNA. PCR and DNA sequencing of DNA extracted from the cDNA library revealed the presence of VZV genes 21, 29, 62, and 63, but not VZV genes 4, 10, 40, 51, and 61, in the enriched cDNA library. These findings confirm the detection of VZV gene 29 and 62 transcripts on Northern (RNA) blots prepared from latently infected human ganglia (J.L. Meier, R.P. Holman, K.D. Croen, J.E. Smialek, and S.E. Straus, Virology 193:193-200, 1993) and the presence of VZV gene 21 transcripts in a cDNA library from mRNA of latently infected ganglia (R.J. Cohrs, K. Srock, M.B. Barbour, G. Owens, R. Mahalingam, M.E. Devlin, M. Wellish and D.H. Gilden, J. Virol. 68:7900-7908,1994) and also reveal, for the first time, the presence of VZV gene 63 RNA in latently infected human ganglia.